(untitled) (Itinerarios Educativos, 2020)
This paper explores the education system in the province of Santa Fe, Argentina, during the post- 1983 democratic period. A system characterized by the persistence of divergent political cultures with a tradition of constitutional expiration that resists all attempts at comprehensive reform towards a new regulatory pedagogical and educational field. The objective is to identify two reform processes in governmental scenarios of political alternation with a similar result: unfinished education reforms. This objective includes studying tensions, challenges, restrictions, and gravitating actors in terms of political cultures